Effect of Vitamin D Supplementation on the Treatment of Pulmonary Tuberculosis Patients in Different Polymorphisms of the Vitamin D Receptor - Hoda Bavi; Seyed Ahmad Hosseini; Alireza Ekrami; Seyed Mohammad Alavi; Amal Saki Malehi (Advanced Biomedical Research)
Background: Vitamin D leads to the activation of macrophages and limitation of intracellular growth of Mycobacterium tuberculosis. Vitamin D receptor (VDR) gene polymorphisms can facilitate the development of tuberculosis (TB). Therefore, the present study aimed to investigate the effect of vitamin D supplementation on response to treatment in patients with pulmonary TB for different VDR polymorphisms. Materials and Methods: This semiexperimental study was carried out over a 2-year period on 73 patients (37 females; 36 males) who suffered from pulmonary TB. Vitamin D supplement at a daily dose of 800 IU was administered to the patients for 8 weeks. The serum levels of vitamin D were measured by electrochemiluminescence immunoassay. The polymerase chain reaction with a sequence-specific primers technique was used to determine the polymorphisms FOK1, Bsm 1, Apa 1, and Taq1 of VDR gene. Results: The mean serum levels of vitamin D increased significantly after the intervention (44.88 ng/ml vs 27.70 ng/ml, P < 0.001). Those with FF genotype of Fok1 polymorphism had a higher chance of a positive response to treatment compared to the other genotypes (P = 0.044, 95% CI). Bsm1, Apa1, and Taq1 polymorphisms increased the treatment response, which was not statistically significant. Conclusion: The results of this study showed that individuals harboring FF genotype of Fok1 polymorphism had a higher chance of a positive response to treatment with vitamin D compared with other genotypes. Therefore, vitamin D supplement can be an appropriate treatment considering the genetic characteristics of TB patients.